2021
DOI: 10.1053/j.gastro.2020.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Colorectal Cancer Stem Cells in the Age of Single-Cell Omics and Targeted Therapies

Abstract: The cancer stem cell (CSC) concept emerged from the recognition of inherent tumor heterogeneity and suggests that within a given tumor, in analogy to normal tissues, there exists a cellular hierarchy composed of a minority of more primitive cells with enhanced longevity (ie, CSCs) that give rise to shorter-lived, more differentiated cells (ie, cancer bulk populations), which on their own are not capable of tumor perpetuation. CSCs can be responsible for cancer therapeutic resistance to conventional, targeted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 138 publications
(128 reference statements)
0
46
0
Order By: Relevance
“…Colorectal cancer (CRC) is the third most common malignancy worldwide ( Burnett-Hartman et al, 2021 ). Development of CRC is a multifactorial process with known risk factors including older age, male sex, family history, and unhealthy lifestyle including a dysregulated diet with low intake of fresh fruits and vegetables, obesity, smoking, and lack of exercise ( Frank et al, 2021 ; Sehgal et al, 2021 ). As clinical therapy, the first-line chemotherapy includes fluoropyrimidines (5-fluorouracil or capecitabine) alone or combined with leucovorin (LV) as well as other cytotoxic agents, such as oxaliplatin (5-Fu/LV/oxaliplatin FOLFOX) and capecitabine/LV/oxaliplatin [CAPOX]) or irinotecan (5-Fu/LV/irinotecan [FOLFIRI]).…”
Section: Introductionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common malignancy worldwide ( Burnett-Hartman et al, 2021 ). Development of CRC is a multifactorial process with known risk factors including older age, male sex, family history, and unhealthy lifestyle including a dysregulated diet with low intake of fresh fruits and vegetables, obesity, smoking, and lack of exercise ( Frank et al, 2021 ; Sehgal et al, 2021 ). As clinical therapy, the first-line chemotherapy includes fluoropyrimidines (5-fluorouracil or capecitabine) alone or combined with leucovorin (LV) as well as other cytotoxic agents, such as oxaliplatin (5-Fu/LV/oxaliplatin FOLFOX) and capecitabine/LV/oxaliplatin [CAPOX]) or irinotecan (5-Fu/LV/irinotecan [FOLFIRI]).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with low-grade FPR (≀15) showed complete response to CT; however, median-grade FPR (20≄FPR>15) and high-grade FPR (>20) implied chemosensitivity and chemoresistance in CRC patients [16]. In this study, we found that CT-treated FPR>20 patients harbored the highest recurrence and death rates, and similar highest recurrence and death rates were observed in non-CT-treated patients with FPR>20, indicating that the cases with FPR>20 might not bene t from CT, and that these patients may be treated with single-targeted therapy or onco-immunotherapy, combined CT after the surgery [34][35][36]. Moreover, the recurrence and death rates in non-CT treated patients with 20≄FPR>15 were approximately ve times higher than those of the CT-treated cases, suggesting that patients with 20≄FPR>15 were suitable to receive CT and could signi cantly bene t from the treatment.…”
Section: Discussionmentioning
confidence: 63%
“…So the antibody recognizes only the glycosylated form of the molecule. A comparative study of this antibody and another antibody that recognizes the non-glycosylated form showed that only the glycosylation is negatively regulated with differentiation (Florek et al, 2005). In colon cancer, the reduction in population expressing the AC133 epitope and loss of clonogenicity upon differentiation of CSCs did not correspond to a reduction of CD133 promoter activity or its expression at mRNA or protein level (Kemper et al, 2010).…”
Section: Cd133mentioning
confidence: 95%
“…The significance of CD133 signaling was not unraveled for a long time. A report that showed CD133's interaction with cholesterol to act as an organizer for membrane topology was the first report that suggested its role in signaling (Florek et al, 2005). However, its relevance in stem cell biology was not unraveled until a physical interaction of CD133 to p85 subunit of PI3K was shown to activate its catalytic subunit p110 (Wei et al, 2013).…”
Section: Cd133mentioning
confidence: 99%
See 1 more Smart Citation